Relationship between Knowledge, Clothing Cleanliness, Towel Cleanliness and Environmental Sanitation with Scabies Incidents at the Pekanbaru City Child Special Development Institute (LPKA) in 2019 - Ruth Novyna Carolyne T; Namora Lumongga Lubis; Nurmaini Nurmaini (Budapest International Research and Critics University, 2021)
Scabies is a skin disease related to the environment and human behavior. In Indonesia, scabies is still a public health problem. Scabies is found in places with unsanitary environments and poor personal hygiene such as dormitories, Islamic boarding schools and prisons. In LPKA Pekanbaru City, there were 38.33% cases of scabies. This case increased from the previous year, where cases in 2017 were 34%. This study aims to analyze the factors that influence the incidence of scabies in the Class II Class II Special Development Institution for Children in Pekanbaru City in 2019. The research design used was cross sectional with a sample size of 120 children obtained using the total population. The instrument used in this study was a questionnaire. The data obtained in this study were analyzed by univariate, bivariate and multivariate using multiple logistic regression tests. The results showed that there was a relationship between cleanliness of clothes (p = 0.003), cleanliness of towels (p = 0.014), and environmental sanitation (p = 0.042) with the incidence of scabies. Meanwhile, the knowledge variable (p = 0.533) was not related to the incidence of scabies. In this study, if students have poor hygiene clothes, towels, and sanitation, they have the opportunity to experience scabies at the Pekanbaru City Children's Special Development Institute.